Postpubertal gluten challenge in coeliac disease. Issue 11 (November 1989) - Mäki, M; Lähdeaho, M L; Hällström, O; Viander, M; Visakorpi, J K
Abstract : Altogether 38 postpubertal children with coeliac disease were rebiopsied. Mucosal abnormality in nine (24%) of them indicated poor adherence to the diet. Gluten challenge with a diet containing a normal amount of gluten was performed in those 29 patients with a normal mucosa. During challenge, rebiopsy was done when reticulin antibodies turned positive (mean 0.6 years, range 0.2-2.0) or at the end of the two year study. Histologically a clear relapse into coeliac disease was seen in all 23 patients who were positive for reticulin antibodies. At this time gliadin antibodies were positive in all but two. Sixteen (70%) of those who relapsed were completely asymptomatic. Three girls and one boy did not relapse within two years, indicating the possible recovery from coeliac disease to be 11%. All four had undergone gluten challenge earlier in childhood, after initial diagnosis and mucosal recovery, and this had resulted in mucosal relapse. To establish definite postpubertal recovery from coeliac disease in cases with normal mucosa at two years from challenge, further follow up studies of reticulin antibodies and later rebiopsy are needed. The reticulin antibody test seems to be suitable for prediction of mucosal relapse in coeliac disease.